Challenges of Islamic Financial Accounting in the Spin-Off Process of Islamic Business Units within Islamic Financial Institutions - Widy Hastuty HS (SEAN Institute, 2026)
This study aims to analyze the challenges of Islamic financial accounting in the spin-off process of Islamic Business Units (Unit Usaha Syariah/UUS) within Islamic financial institutions in Medan City. The study employed a descriptive qualitative approach, with data collected through in-depth interviews, observations, open-ended questionnaires, and documentation. Research informants were selected using purposive sampling and included management personnel, accounting and finance staff, compliance officers, internal auditors, and other individuals with a comprehensive understanding of Islamic financial accounting practices and the spin-off process. The findings reveal that the primary challenges in the spin-off process are associated with the separation of assets and liabilities, the readiness of accounting information systems, the implementation of Islamic accounting standards, the quality of human resources, the documentation of Sharia contracts (akad), and the preparation of independent financial statements. The Islamic Business Unit of Bank Sumut served as the institution most directly relevant to the spin-off issue, while institutions that had already transformed into Islamic Commercial Banks (Bank Umum Syariah/BUS) and non-bank Islamic financial institutions were used as comparative cases for Islamic accounting practices. The study concludes that the success of the spin-off process depends not only on regulatory and institutional readiness but also on the preparedness of Islamic financial accounting systems that are well-organized, transparent, and fully compliant with Sharia principles.